Improving imbalance classification via ensemble learning based on two-stage learning - Liu, Na; Wang, Jiaqi; Zhu, Yongtong; Wan, Lihong; Li, Qingdu (Frontiers in Computational Neuroscience, 2024)
The excellent performance of deep neural networks on image classification tasks depends on the large-scale high-quality dataset. However, the dataset collected from the real world are typically biased in their distribution, which will lead to a sharp decline in model performance. The main reason is that imbalance distribution results in the prior shift and covariate shift. Recent researches usually use a two-stage learning method consisting of two rebalancing strategies to solve these problems, but the combination of partial rebalancing strategies will damage the representational ability of networks. Besides, the two-stage learning method has little helpful on addressing the problem of covariate shift. To solve the above two issues, we first propose a sample logit aware reweighting method called (SLA), which can not only repair the weights of majority class hard samples and minority class samples but also will integrate with logit adjustment to form a stable two-stage learning strategy. Secondly, to solve the covariate shift problem, inspired by ensembling learning, we propose a multi-domain expert specialization model, which can achieve a more comprehensive decision by averaging expert classification results from multiple different domains. Finally, we combine SLA and logit adjustment into a two-stage leraning method and apply our model to the CIFAR-LT and ImageNet-LT datasets. Compared with the most advanced methods, our experimental results show excellent performance.